Solutions to improve business performance in Hoang Long Mechanics technology joint stock company = Giải pháp nâng cao hiệu quả hoạt động kinh doanh tại công ty cổ phần cơ khí công nghệ Hoàng Long - Phan, Tiến Thành (2020)
The author have a system of theoretical, updated knowledge, and research methods for management. Assess the status of Hoang Long Jsc Company. On the basis of analyzing and evaluating the business results that Hoang Long Mechanical Engineering Joint Stock Company has achieved through the years 2016-2018, the author accurately investigates the business performance and the situation of the company. capital using, asset using situation, solvency of the company, find out the limitations that exist in the company. Proposing solutions and business orientation for the next period, helping to improve the remaining limitations and promoting the company's potentials, contributing to improving business performance.